Synthesis and enhanced photoelectrocatalytic activity of p–n junction Co3O4/TiO2 nanotube arrays - Dai, Gaopeng; Liu, Suqin; Liang, Ying; Luo, Tianxiong (Applied surface science, 2013)
► Co3O4/TiO2 nanotube arrays (NTs) were prepared by an impregnating–deposition–decompostion method treatment. ► Co3O4/TiO2 NTs exhibit high photoelectrocatalytic (PEC) activity. ► The high PEC activity was attribute to the formation of p–n junction between Co3O4 and TiO2. Co3O4/TiO2 nanotube arrays (NTs) were prepared by depositing Co3O4 nanoparticles (NPs) on the tube wall of the self-organized TiO2 NTs using an impregnating–deposition–decompostion method. The prepared samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and UV–vis absorption spectroscopy. The photoelectrocatalytic (PEC) activity is evaluated by degradation of methyl orange (MO) aqueous solution. The prepared Co3O4/TiO2 NTs exhibit much higher PEC activity than TiO2 NTs due to the p–n junction formed between Co3O4 and TiO2.